Pengaruh Capital Intencity dan Komite Audit terhadap Agretivitas Pajak - Dinar Ambarita (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Taxes represent a significant cost for companies and directly affect profitability and firm value, encouraging managers to seek strategies that reduce tax burdens. This condition has raised concerns regarding tax aggressiveness, particularly in capital-intensive and highly regulated industries such as the energy sector. This study aims to provide empirical evidence on the influence of capital intensity, the audit committee, and political connections on tax aggressiveness in energy companies listed on the Indonesia Stock Exchange (IDX). Using a quantitative associative research design, the study examines 13 energy companies observed over the 2019–2023 period, resulting in 65 firm-year observations selected through purposive sampling. Secondary data were analyzed using Microsoft Excel and EViews 13. The analytical procedures included descriptive statistics, model selection tests, and classical assumption tests, coefficient of determination analysis, panel data regression, as well as F-tests and t-tests. The results indicate that firm characteristics and corporate governance mechanisms collectively play an important role in shaping corporate tax behavior. Capital intensity is associated with lower levels of tax aggressiveness, suggesting that higher fixed-asset investment increases transparency and regulatory scrutiny. The audit committee variable shows a tendency to encourage more aggressive tax planning, possibly reflecting greater managerial confidence in managing tax risks. In contrast, political connections do not appear to significantly influence tax aggressiveness, implying that regulatory enforcement reduces their effectiveness. Overall, this study contributes to the literature by clarifying inconsistent prior findings and highlighting the role of internal governance in corporate tax decisions.